CCAFS project low emissions development of the Chinese dairy sector - Vries, Marion de; Zijlstra, Jelle (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Part of the Carbon Footprint Assessment and Mitigation Options of Dairy under Chinese Conditions Project. Implemented by the Chinese Academy of Agricultural Sciecnces (CAAS), China Agricultural University (CAU) & Wageningen University and Research (WUR). In collaboration with the CGIAR Research Program for Climate Change, Agriculture and Food Security (CCAFS) and the Sino-Dutch Dairy Development Centre (SDDDC).